Evaluasi Atas Implementasi Budaya Risiko Pada Perusahaan Finansial ABC - Br Karo Sekali, Rehulina (Politeknik Ganesha Medan, 2024)
The aim of this research is to obtain on the company’s risk culture that has been implemented by the company by assessing their individual perspective and organizational perspective. Data were collected with method which is survey and interview. The surveys distributed to all staff at lower to middle management level of employee to seek individual perspective and the interview held to upper level of management to seek organization perspective. The IRM Risk Culture framework took place to evaluate how did the risk culture went within the organization. The research found out that employee’s type of the company has the types of risk perspective as deliberate and composed, which means it has a medium to high risk tolerance. Based on ethical decision-making using in general, the entire group tends to make decisions based on conscience ethics that prioritize empathy, care, and respect. The existing organizational culture in the company based on the social and solidarity dimensions has a high level of solidarity and socialization or called as communal category. The Communal category is characterized by fair risk distribution among employees, good teamwork among functions and locations, and close relationships between individuals. Regarding the evaluation of the eight aspects of risk culture (IRM Aspect Model) from the social and solidarity perspective, there are four aspects that do not meet the expectations of the IRM. These aspects are Risk Decision, Risk Resource, Responding to Bad News, and Reward. Keywords: Risk Culture, Organization Culture, Risk Management